2020
DOI: 10.1038/s41598-020-65795-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an external magnetic field on microbial functional genes and metabolism of activated sludge based on metagenomic sequencing

Abstract: This study explored the effect of 70-mT magnetic field on wastewater treatment capacity for activated sludge in long-term laboratory-scale experiments. Metagenomic sequencing were conducted based on Illumina HiSeq 2000 platform after DNA extraction of the activated sludge. Then the effect of the magnetic field on the microbial unigene and metabolic pathways in activated sludge was investigated. As a result, higher pollutant removal was observed at 70 mT, with which the elimination of total nitrogen (TN) was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This is because the use of a magnetic field can enhance the way the system performs physically to solid–liquid separation due to the clustering of colloidal particles. Additionally, the use of magnetic fields can affect the biological properties due to the enhancement of the bacterial activity, which increased the current density of the ES [ 19 , 38 ]. However, the higher intensity and the longer exposure duration after day 8 reduced the current density of the ES, which consequently reduced the biogas accumulation ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the use of a magnetic field can enhance the way the system performs physically to solid–liquid separation due to the clustering of colloidal particles. Additionally, the use of magnetic fields can affect the biological properties due to the enhancement of the bacterial activity, which increased the current density of the ES [ 19 , 38 ]. However, the higher intensity and the longer exposure duration after day 8 reduced the current density of the ES, which consequently reduced the biogas accumulation ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, researchers are trying to improve the performance of the traditional anaerobic digestion process, mainly because the process has low contaminant removal levels, low microbial activity, and low methane production. The use of an electromagnetic field together with the anaerobic digestion process has been shown to have a great deal of potential due to the greater enhancement of bacterial activity and the higher methane production [ 19 , 20 ]. Interestingly, current studies have shown a more positive effect for the use of a bioelectrochemical system in anaerobic digestion; the use of a bioelectrochemical system enhances the biological activity as well as the electrochemical efficiencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few decades, numerous studies have revealed that MFs can virtually all affect living organisms, ranging from bacteria to human beings, [ 9 , 50 , 51 , 52 , 53 ]. However, the underlying mechanisms are still unclear [ 54 , 55 ], especially the impact of SMF on filamentous fungi. Therefore, we explored the effect of SMF on M. ruber M7 and its related molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Li et al 18 found that adding 100-mT MF promoted the maximum voltage of Shewanella-inoculated MFCs that might be because of the oxidative stress mechanism to enhance bioelectrochemical activity. Geng et al 40 studied the effects of an external MF with 70 mT MF on microbial metabolism. The results showed that MF could change the abundance of functional genes, which contents of environmental information processing, cellular processes, genetic information processing, human diseases, and organismal systems.…”
Section: Mf Effect On Microorganism Communitymentioning
confidence: 99%